2015
DOI: 10.3357/amhp.4075.2015
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The Risk of Prostate Cancer in Pilots: A Meta-Analysis

Abstract: Pilots are at least twice as likely to develop prostate cancer compared to the general population. The implications of these findings are important considering the high prevalence of prostate cancer and the large number of pilots in the workforce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Shift work as a possible cause of prostate cancer has been reviewed thoroughly, but results were inconclusive [47–55]. Several mechanisms are proposed to explain the association of prostate cancer and shift workers.…”
Section: Discussionmentioning
confidence: 99%
“…Shift work as a possible cause of prostate cancer has been reviewed thoroughly, but results were inconclusive [47–55]. Several mechanisms are proposed to explain the association of prostate cancer and shift workers.…”
Section: Discussionmentioning
confidence: 99%
“…Ассоциировано с повышенным риском смерти от РПЖ [19] Гонорея Достоверная корреляция с увеличением выявления РПЖ [20] Работа по ночам Повышенный риск выявления РПЖ [21] Профессиональная лучевая нагрузка (пилоты авиации) Повышенный риск выявления РПЖ [22] Активные курильщики Повышение риска смерти от РПЖ [23] Вазэктомия Не ассоциирована с повышением риска возникновения РПЖ [24] Ацетилсалициловая кислота и нестероидные противовоспалительные препараты Разноречивые данные о влиянии приема ацетилсалициловой кислоты и нестероидные противовоспалительные препараты на риск возникновения РПЖ [25,26] Ультрафиолетовое излучение Уменьшает риск возникновения РПЖ [27] Циркумцизия Уменьшает риск возникновения РПЖ [28] Частота эякуляции (≥21 раз в месяц по сравнению с 4-7 раз в месяц) Частая эякуляция способствует снижению риска возникновения РПЖ на 20% [29] N -регионарные ЛУ…”
Section: облысениеunclassified
“…Epidemiological evidence so far points to the connections between PCa and CRD. Meta-analyses on the health outcomes of airplane pilots [ 18 , 19 ] and studies on female night shift nurses [ 20 ] have demonstrated the contribution of CRD (due to jetlag or night shift work) to both prostate and breast cancer [ 21 ]. Sleep disruption and light-induced melatonin suppression, both related outcomes of CRD, are associated with an increased risk for advanced PCa [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%